The relationship between gut microbiota and inflammatory response, learning and memory in mice by sleep deprivation - Zhang, Mengjie; Zhang, Mengying; Kou, Guangning; Li, Yan (Frontiers in Cellular and Infection Microbiology, 2023)
Objective Sleep deprivation has developed into a common phenomenon, which can lead to inflammatory responses and cognitive impairment, but the underlying mechanism is ambiguous. Emerging evidence shows that gut microbiota plays a crucial role in theoccurrence and development of inflammatory and psychiatric diseases, possibly through neuroinflammation and the brain-gut axis. The current study investigated the influence of sleep deprivation on gut microbiota composition, pro-inflammatory cytokines, learning and memory in mice. Further, it explored whether changes in gut microbiota increase pro-inflammatory cytokine and induce learning and memory impairment. Methods Healthy 8-week-old male C57BL/6J mice were randomly divided into the regular control group (RC), environmental control group (EC), and sleep deprivation group (SD). The sleep deprivation model was established by the Modified Multiple Platform Method. The experimental mice were subjected to sleep deprivation for 6h/d (8:00 am∼14:00 pm) in a sleep deprivation chamber, and the duration of sleep deprivation was 8 weeks. Morris water maze test to assess learning and memory in mice. Enzyme-Linked Immunosorbent Assay determined the concentrations of inflammatory cytokines. The changes in gut microbiota in mice were analyzed by 16S rRNA sequencing. Results We found that SD mice had elevated latency of exploration to reach the hidden platform (p>0.05) and significantly decreased traversing times, swimming distance, and swimming time in the target zone when the hidden platform was removed (p<0.05). Sleep deprivation caused dysregulated expression in serum IL-1β, IL-6, and TNF-α in mice, and the difference was significant (all p<0.001). Tannerellaceae, Rhodospirillales, Alistipes, and Parabacteroides were significantly increased in SD mice. Correlation analysis showed IL-1β was positively correlated with the abundance of Muribaculaceae (r=0.497, p<0.05) and negatively correlated with the abundance of Lachnospiraceae (r=-0.583, p<0.05). The TNF-α was positively correlated with the abundances of Erysipelotrichaceae, Burkholderiaceae, and Tannerellaceae (r=0.492, r=0.646, r=0.726, all p<0.05). Conclusion Sleep deprivation can increase pro-inflammatory cytokine responses and learning and memory impairment in mice and may be caused by the disorder of the microbiota. These findings of this study may open avenues for potential interventions that can relieve the detrimental consequences of sleep loss.